First evidence for thermal tolerance benefits of the bacterial symbiont Cardinium in an invasive whitefly, Bemisia tabaci. Issue 11 (19th July 2021) - Yang, Kun; Yuan, Meng‐Ying; Liu, Ying; Guo, Chen‐Liang; Liu, Tong‐Xian; Zhang, You‐Jun; Chu, Dong
Abstract: BACKGROUD: Cardinium symbiont is a maternally inherited bacterial endosymbiont and widely spreads in arthropods including Bemisia tabaci (Hemiptera: Aleyrodidae). However, the potential role of Cardinium played in the biology of their hosts is largely unknown. In two genetic lines (i.e. LS and SG lines) of B. tabaci MED, collected from different locations in China, we tested the effects of Cardinium on the performance of the host whitefly under a constant high temperature (31 °C) using the age‐stage two‐sex life table method, and explored the genes influenced by Cardinium ‐infection by RNA‐sequencing. RESULTS: We found that Cardinium did provide protection of B. tabaci against heat stress under 31 °C. However, there was a significant connection between Cardinium ‐infection and whitefly genetic backgrounds. Performance revealed that Cardinium infection can increase the longevity of both female and male adults and oviposition periods in both lines, but it also conferred benefits of fecundity and pre‐adult period to LS line. Additionally, the population parameters such as intrinsic rate of increase ( r ), finite rate of increase ( λ ) and mean generation time ( T ) demonstrated that Cardinium infection conferred fitness benefits to LS line but not to SG line. Transcriptome analysis indicated that several genes related to homeostasis and metamorphosis such as ubiquitin‐related genes were highly expressed in Cardinium ‐infected B. tabaci . CONCLUSION: The research provided the first evidence that Cardinium can increase the thermal tolerance of whitefly, which may be associated with host genetic background. Abstract : The comparison of the survival rate and fitness in Cardinium ‐infected and ‐uninfected Bemisia tabaci MED under high temperature showed that Cardnium infection could increase the thermal tolerance of B. tabaci . Transcriptome analysis revealed that several genes related to homeostasis and metamorphosis were highly expressed in Cardinium ‐infected B. tabaci . © 2021 Society of Chemical Industry.